Usability- and Accessibility-Focused Requirements Engineering First International Workshop, UsARE 2012, Held in Conjunction with ICSE 2012, Zurich, Switzerland, June 4, 2012 and Second International Workshop, UsARE 2014, Held in Conjunction with RE 2014, Karlskrona, Sweden, August 25, 2014, Revised Selected Papers - Ebert, Achim; Humayoun, Shah Rukh; Seyff, Norbert; Perini, Anna; Barbosa, Simone D.J (Programming and Software Engineering, 2016)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Workshop on Usability and Accessibility focused Requirements Engineering, UsARE 2012, held in Zurich, Switzerland, in June 2012 in conjunction with ICSE 2012, the 34th International Conference on Software Engineering, and the Second International Workshop, UsARE 2014, held in Karlskrona, Sweden, in August 2014, in the course of RE 2014, the 22nd International Requirements Engineering Conference. This book consists of 10 chapters of which 9 are extended versions of the papers presented at the two UsARE events. Amongst them, 3 are extended versions of the papers presented at UsARE 2012 and 6 are extended versions of papers presented at UsARE 2014 - rounded off by a new chapter that was added as authors are doing relevant work on the same topic. The chapters are organized into three sections according to their main focus: usability and user experience, accessibility and applications.